THE IMPLEMENTATION OF A MANAGEMENT AUDITON HR RECRUITMENT TO ASSESS THE EFFECTIVENESS OF EMPLOYEE PERFORMANCE - Dirvi Surya Abbas; Tubagus Ismail; Muhamad Taqi; Helmi Yazid (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
The purpose of this study was to determine the effect of audit planning, recruitment and selection and placement of human resources on the performance of company employees at Pt Indo Taichen Textile Industry. The population of this study includes all parts and divisions of Pt Indo Taichen Textile Industry. The sampling technique used was purposive sampling technique. The type of data used is primary data from interviews and observations to companies and secondary data obtained from company audit reports. The analytical technique used is multiple linear regression analysis using SPSS 26 software. The results showed that the planning audit partially had a significant positive effect on employee performance, the recruitment audit partially had no significant effect on employee performance, and the selection and placement audit partially did not have a significant effect on employee performance. The results of this simultaneous study indicate that the Human Resources (HR) audit affects improvements in improving the performance of company employees, because companies that have carried out audits can find out what HR programs have not been fulfilled, repaired and improved again by the Company.